Review of financial vulnerability studies - Lee, May Poh; Sabri, Mohamad Fazli (Society for Science and Education, 2017)
Financial vulnerability has become an emerging concern to many parties and a number of factors in households’ financial vulnerability are believed to influence households’ financial well-being. Financial vulnerability is a status of financial instability or a situation to the exposure of financial risk and shock. Thus, the focus of this paper is to overcome the problem of how to justify the variables of financial vulnerability in order to achieve the financial well-being among the households. Moreover, this current paper concludes the financial vulnerability studies in eight countries which provide the similarities and differences in measuring financial vulnerability. Hence, the evidence review revealed that high financial vulnerable households are characterized by low income or low liquid assets, high balance sheet leverage, disability to cope with financial stress and financial crisis.